2007
DOI: 10.1113/jphysiol.2007.136796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glucocorticoid‐regulated genes that control cell proliferation during murine respiratory development

Abstract: Glucocorticoids play a vital role in fetal respiratory development and act via the intracellular glucocorticoid receptor (GR) to regulate transcription of key target genes. GR-null mice die at birth due to respiratory dysfunction associated with hypercellularity and atelectasis. To identify events associated with this lung phenotype we examined perinatal cellular proliferation rates and apoptotic indices. We demonstrate that compared to wild-type controls, day 18.5 postcoitum (p.c.) GR-null mouse lungs display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
3

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
2
37
3
Order By: Relevance
“…In normal lung array data, the serine protease CELA1 increased threefold between E12 and PND1, and gene expression remained at that level through adulthood (22). In glucocorticoid receptor-null mouse lung array data, at E18.5, expression of CELA1 was reduced 9.4-fold compared with wild type, and PCR confirmation demonstrated a 25-fold decrease in CELA1 mRNA (7). Microarray data demonstrated no differences in CELA1 expression in the hyperoxia model of impaired lung development (12).…”
Section: Temporal-spatial Changes In Elastin Remodeling During Sacculmentioning
confidence: 96%
See 1 more Smart Citation
“…In normal lung array data, the serine protease CELA1 increased threefold between E12 and PND1, and gene expression remained at that level through adulthood (22). In glucocorticoid receptor-null mouse lung array data, at E18.5, expression of CELA1 was reduced 9.4-fold compared with wild type, and PCR confirmation demonstrated a 25-fold decrease in CELA1 mRNA (7). Microarray data demonstrated no differences in CELA1 expression in the hyperoxia model of impaired lung development (12).…”
Section: Temporal-spatial Changes In Elastin Remodeling During Sacculmentioning
confidence: 96%
“…In a mouse pup mechanical ventilation model, inhibition of neutrophil elastase improves alveolar septation (18). While investigating the effect of glucocorticoid-receptor signaling on lung cell proliferation during embryonic lung development, Bird et al found a 25-fold reduction in mRNA levels of the pancreatic serine protease chymotrypsin-like elastase 1 (CELA1) (7). Published microarray data of normally developing mouse lung demonstrated increased CELA1 mRNA starting at embryonic day 14 (22).…”
mentioning
confidence: 99%
“…39) In addition, it has been reported that GR regulates various gene transcription. 40) Transcription activity of some genes related to cell cycle, such as cyclin, might be altered by CORT treatment. 41) In contrast, the expression level of MR did not change in either the cytosol or nuclear fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are known M2 polarizing stimuli and in a microarray study of glucocorticoid-responsive genes, the gene most significantly reduced in embryonic glucocorticoid receptor deficient mice is the M2 polarization-associated gene Chi3l3. 142 They are particularly associated with the M2a subset, which aside from Th2 responses is also linked to negative aspects including ECM production and allergy. 48,51 The effect of such medications on developmental macrophages requires examination to ascertain if inappropriate skewing of macrophage phenotype may contribute to some of the negative side effects of glucocorticoid treatment.…”
Section: Csf-1 and Macrophage Manipulation In Developmentmentioning
confidence: 99%